Development of Bruton's Tyrosine Kinase Inhibitors for Rheumatoid Arthritis - Lv, Jiahui; Wu, Jingde; He, Feng; Qu, Ying; Zhang, Qiuqiong; Yu, Chenggong (Current Medicinal Chemistry, 2018)
Rheumatoid Arthritis (RA) is a chronic autoimmune disease and becomes one of the major causes of disability and work force loss. The presence of abnormal B cell and autoantibodies produced by most RA patients, primarily ACPA and RF, indicate that the function of B cell was involved in the development of RA disease. Accordingly, the drug targeting B cell has become a hot spot in the treatment of RA. Studies have shown that Bruton's tyrosine kinase (BTK) is involved in the regulation of B cell proliferation and activation process. Some small molecule BTK inhibitors have shown excellent inhibition in biological activity analysis and animal models. Therefore, this review will briefly introduce BTK and its role in cell signaling and overview recent progress of BTK inhibitors for RA treatment.
Keywords: BTK inhibitor